Achieving global targets on breastfeeding in Thailand: gap analysis and solutions - Chompoonut Topothai; Viroj Tangcharoensathien (BMC, 2021)
Abstract Background Global advocates for breastfeeding were evident since the International Code of Marketing of Breast-Milk Substitutes (BMS Code) was adopted in 1981 and fostered by subsequent relevant World Health Assembly resolutions, using a framework that promotes, supports and protects breastfeeding. Global partners provided comprehensive support for countries to achieve breastfeeding targets while progress was closely monitored. This review identifies breastfeeding policy and implementation gaps in Thailand. Main findings Although Thailand implemented three Thai voluntary BMS Codes, ineffective enforcement results in constant violations by BMS industries. In light of strong resistance by the BMS industries and their proxies, it was not until 2017 that the Code was legislated into national law; however regulatory enforcement is a protracted challenge. A Baby-Friendly Hospital Initiative (BFHI), mostly in public hospitals, was successfully applied and scaled up nationwide in 1992, but it later became inactive due to lack of continued support. Several community-based and workplace programmes, which supported breastfeeding, also faced challenges from competing agendas. Although the Labor Protection Law offers 98 days maternity leave with full pay, the conducive environment for successful six- month exclusive breastfeeding (EBF) needs a significant boost. These gaps in policy were exacerbated by a lack of multi-sectoral collaboration, ineffective implementation of existing interventions, inadequate investment, and lack of political will to legislate six-month maternity leave. As a result, the progress of EBF rate during the first 6 months as measured by previous 24 h was erratic; it increased from 12.3% in 2012 to 23.1% in 2015 and decreased to 14% in 2019. There was a deterioration of early initiation from 49.6% in 2006 to 34% in 2019. These low performances hamper the achievement of global targets by 2030. Conclusions We recommend the following. First, increase financial and human resource investment, and support successful exclusive breastfeeding in BHFI, communities and workplaces through multi-sectoral actions for health. Second, implement the active surveillance of violations and strengthen law enforcement for timely legal sanctions of violators. Third, revitalize the BFHI implementation in public hospitals and extend to private hospitals.